Do statins benefit low-risk population for primary prevention of atherosclerotic cardiovascular disease: A retrospective cohort study - Ryou, In Sun; Kim, Ju Young; Park, Hwa Yeon; Oh, Sohee; Kim, Sehun; Kim, Hwa Jung (Frontiers in Medicine, 2022)
The reported beneficial effects of statins on cardiovascular outcome based on risk assessment are inconsistent. Therefore, we investigated statin therapy effectiveness for the primary prevention of cardiovascular disease (CVD), according to the Korean Risk Prediction Model (KRPM). Subjects aged 40–79 years with low density lipoprotein cholesterol (LDL-C) of <190 mg/dL and without CVD history were categorized as statin users or non-users using the National Health Insurance Service-National Sample Cohort (NHIS-NSC) database, Korea, 2002–2015. The 10-year atherosclerotic CVD (ASCVD) risk was calculated using the validated KRPM and categorized as low, borderline, intermediate, or high-risk groups; the incidence of major adverse cardiovascular events (MACEs) was compared over a mean follow-up period of 5.7 years using Cox proportional hazard models. The MACE incidence risk was decreased in statin users [hazard ratio (HR) 0.90, 95% confidence interval (CI) (0.84–0.98)]. However, there was an increased risk of MACE incidence in low-risk statin users [HR 1.80, 95% CI (1.29–2.52)], and no significant relationship was identified between statin use and MACE in the borderline [HR 1.15, 95% CI (0.86–1.54)] and intermediate-risk [HR 0.94, 95% CI (0.85–1.03)] groups. The risk of MACE incidence decreased only in the high CVD risk group among statin users. Statin use is not associated with MACE reduction in low- to intermediate-risk participants. Therefore, individuals with LDL-C level of <190 mg/dL and low ASCVD risk should consider statin therapy only when CVD risk is proved obvious using an appropriate ASCVD risk tool.